Intraperitoneal administration of activated protein C prevents postsurgical adhesion band formation - Dinarvand, Peyman; Hassanian, Seyed Mahdi; Weiler, Hartmut; Rezaie, Alireza R (Blood, 2015)
Postsurgical peritoneal adhesion bands are the most important causes of intestinal obstruction, pelvic pain, and female infertility. In this study, we used a mouse model of adhesion and compared the protective effect of activated protein C (APC) to that of the Food and Drug Administration-approved antiadhesion agent, sodium hyaluronate/carboxymethylcellulose (Seprafilm) by intraperitoneal administration of either APC or Seprafilm to experimental animals. Pathological adhesion bands were graded on day 7, and peritoneal fluid concentrations of tissue plasminogen activator (tPA), d-dimer, thrombin-antithrombin complex, and cytokines (IL-1β, IL-6, interferon-γ, tumor necrosis factor-α, transforming growth factor-β1) were evaluated. Inflammation scores were also measured based on histologic data obtained from peritoneal tissues. Relative to Seprafilm, intraperitoneal administration of human APC led to significantly higher reduction of postsurgical adhesion bands. Moreover, a markedly lower inflammation score was obtained in the adhesive tissues of the APC-treated group, which correlated with significantly reduced peritoneal concentrations of proinflammatory cytokines and an elevated tPA level. Further studies using variants of human APC with or without protease-activated receptor 1 (PAR1) signaling function and mutant mice deficient for either endothelial protein C receptor (EPCR) or PAR1 revealed that the EPCR-dependent signaling activity of APC is primarily responsible for its protective activity in this model. These results suggest APC has therapeutic potential for preventing postsurgical adhesion bands.